Functional Nanomaterials and Polymer Nanocomposites: Current Uses and Potential Applications - Yadav, Raghvendra Singh (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This book covers a broad range of subjects, from smart nanoparticles and polymer nanocomposite synthesis and the study of their fundamental properties to the fabrication and characterization of devices and emerging technologies with smart nanoparticles and polymer integration.